POGROMS IN GANDZAK (KIROVABAD) AS ANOTHER MANIFESTATION OF GENOCIDAL POLICY IN AZERBAIJAN - Avanesyan, Iskuhi (Armenian Folia Anglistika, 2025)
the context of the nationwide movement in Nagorno-Karabakh in 1988, the anti-Armenian policy in Azerbaijan took the form of a large-scale and regular violence. The pogroms against Armenians organized on 27-29 February 1988 in the city of Sumgait (Azerbaijan) marked the beginning of a new stage of discriminatory policy against Armenians, which was to organize regular mass pogroms against Armenians. The next waves of Sumgayit crimes took place in November 1988 in Gandzak (Kirovabad) and nearby Armenian-populated areas, and in January 1990 in Baku.The purpose of this article is to highlight the pogroms committed by Soviet Azerbaijan in 1988 against the Armenian population of Gandzak (Kirovabad) and their consequences. The research suggests that the pogroms organized against the Armenians in Gandzak (Kirovabad) and nearby settlements in 1988 were motivated by national hatred and aimed at the physical destruction of a specific nation, the Armenians. The research shows that the pogroms against Armenians in Gandzak (Kirovabad) were organized with the cooperation of local authorities and law enforcement agencies, and the aim of the pogroms was to kill and deport Armenians. The methodological basis of the article is the methods of analysis, research of facts, and comparison of various materials.As a result of the study, we conclude that Azerbaijan committed a crime against the Armenian population of its republic during the Soviet years - ethnic cleansing, which was also a manifestation of Armenianophobia.
Keywords: Armenianophobia; intimidation; demonstrations; attack; violence; pogroms; self-defense; impunity